The natural course of hepatitis C virus infection after 22 years in a unique homogenous cohort: spontaneous viral clearance and chronic HCV infection. Issue 3 (1st September 2001) - Barrett, S; Goh, J; Coughlan, B; Ryan, E; Stewart, S; Cockram, A; O'Keane, J C; Crowe, J
Abstract : BACKGROUND/AIMS: The cohort of Irish women infected with hepatitis C virus (HCV) genotype 1b via contaminated anti-D immunoglobulin in 1977 represent a unique homogenous group to investigate the natural course of HCV infection. METHODS: The clinical status of 87 polymerase chain reaction (PCR) positive and 68 PCR negative women was investigated at diagnosis (1994/95) and after 4–5 years of follow up (21/22 years after inoculation). Other features investigated included: histological status/progression, psychosocial impact of HCV infection, extrahepatic manifestations, and HLA class II associations. RESULTS: The most common symptoms reported were fatigue and arthralgia. Furthermore, 77% of women fell within the clinical range for psychological distress. A history of icteric hepatitis was reported in 20.6% of PCR negative and 3.4% of PCR positive women after inoculation (p=0.002). The mean histological activity index/fibrosis scores of PCR positive and negative women were 4.1 (1.4)/1.1 (1.3) and 2.1 (1.5)/0.15 (0.36) at diagnosis and 4.1 (1.2)/1.0 (1.0) in 44 PCR positive women after five years of follow up. Cirrhosis or hepatocellular carcinoma was not observed. The DRB1*01 allele was present in 28.8% of PCR negative and 8.7% of PCR positive women (p=0.004). The prevalence rates of mixed cryoglobulinaemia, sicca complex, positive thyroid autoantibodies, antinuclear antibody, rheumatoid factor, and antimitochondrial antibody in PCR positive women were 12.7%, 7.6%, 13.9%, 5.1%, 3.8%, and 3.8%. CONCLUSIONS: A benign course of HCV infection with lack of disease progression was observed in women with chronic HCV, 22 years after inoculation. Acute icteric hepatitis and the HLA DRB1*01 allele were associated with viral clearance. Despite this favourable outcome, high levels of psychological distress and poor quality of life were present.